2007
DOI: 10.1111/j.1540-8159.2007.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Abnormal Microvolt T‐Wave Alternans and Poor Glycemic Control in Type 2 Diabetic Patients

Abstract: Our findings suggest that abnormal TWA is a very common condition (approximately 25%) among people with type 2 diabetes without manifest CVD and is closely correlated to glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 22 publications
2
44
0
Order By: Relevance
“…The prevalence is similar to previous heart failure and cardiomyopathy studies (14,17), although the patients in our cohort had preserved LV function on CMR (ejection fraction 61.9 Ϯ 15.3%). Nonetheless, when compared with studies in patients with diabetes mellitus (approximately 25%) or healthy individuals (approximately 6%), ESRD patients have a higher rate of abnormal results (16,18).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The prevalence is similar to previous heart failure and cardiomyopathy studies (14,17), although the patients in our cohort had preserved LV function on CMR (ejection fraction 61.9 Ϯ 15.3%). Nonetheless, when compared with studies in patients with diabetes mellitus (approximately 25%) or healthy individuals (approximately 6%), ESRD patients have a higher rate of abnormal results (16,18).…”
Section: Discussionmentioning
confidence: 86%
“…CMR demonstrated a lower ejection fraction, higher LVMI, and higher LV chamber size in the ESRD group compared with the LVH patients. Presence of LVH was high in both groups and despite LVH patients being recruited based on previous echocardiography, only 18 (60%) had LVH on CMR.…”
Section: Comparison Between Esrd and Lvh Patientsmentioning
confidence: 89%
See 1 more Smart Citation
“…There are several studies showing, marked QTc prolongation in diabetic patients [31] . Another strong predictor of VA, microvolt T wave alternans (TWA) measurement, has been studied in type 2 diabetic patients without known CVD, considering the glycemic status in each patient (which is reflected by HbA1c levels) [32] . In this small study, the frequencies of atypical TWA patients were significantly higher than the control group.…”
Section: Diabetes and Ventricular Arrhythmiasmentioning
confidence: 99%
“…8 -10 Recently, we found that the prevalence of abnormal MTWA was Ϸ5-fold greater in T2DM patients without a history of myocardial infarction than in matched nondiabetic control subjects and it was strongly correlated with glycemic control. 13 It has been reported that MTWA is influenced by myocardial ischemia, 14 increased sympathetic tone, 15 emotional arousal, 16 LV hypertrophy, 17 and LV end-diastolic volume (EDV) in dilated cardiomyopathy. 18 However, there is uncertainty as to whether central or peripheral hemodynamic factors are associated with MTWA abnormality in T2DM individuals without LV systolic dysfunction.…”
Section: Clinical Perspective On P 414mentioning
confidence: 99%